‘Partakers of the Divine Nature’: Ripley’s Discourses and the Transcendental Annus Mirabilis - David M. Robinson (Religions, 2018)
In declaring 1836 the “Annus Mirabilis” of Transcendentalism, Perry Miller captured the emerging vitality of a new religious movement, described by Convers Francis as “the spiritual philosophy”. Francis first listed George Ripley’s Discourses on the Philosophy of Religion (1836) as a sign of the new movement. Ripley’s book, strongly influenced by William Ellery Channing’s sermon “Likeness to God” (1828), captured the metamorphosis of Transcendentalism from its Unitarian theological roots, and sheds light on the Transcendentalists’ theory of religious experience. Ripley presented Transcendentalism as the purist form of Christian theology. This new religious awareness enabled a realization of the divine “inner nature”, and described a religious life dedicated to the practice of spiritual self-cultivation. This new awareness brought with it “universal love”, and a vision of what it meant to partake of divinity.